GDP at risk in a DSGE model: an application to banking sector stress testing - Esa Jokivuolle; Juha Kilponen; Tero Kuusi (Bank of Finland, 2007)
We suggest a complementary tool for financial stability analysis based on stochastic simulation of a dynamic stochastic general equilibrium model (DSGE) of the macro economy. The paper relates to financial stability research in which financial aggregates crucial to financial stability are modelled as functions of macroeconomic variables. In these models, stress tests for eg banking sector loan losses can be generated by considering adverse scenarios of macro variables. A DSGE model provides a systematic way of generating coherent macro scenarios which can be given a rigorous economic interpretation. The approach is illustrated using a DSGE model of the Finnish economy and a simple model of Finnish banking sector loan losses.
URN:NBN:fi:bof-20140807331
Keywords: E13; E37; G21; G28; 330; DSGE models; financial stability; loan losses; stress testing